Hak Atas Pendidikan di Kabupaten Indragiri Hilir: Strategi Mewujudkan Akses dan Kesetaraan Pendidikan Inklusif - Rezal, Muhammad; Nurjannah, Nurjannah; Ramadhani, Alifa Zahro; Rahmawati, Fitri; Putri, Sintia Salsabila; Dongoran, Rachel F B; Hambali, Hambali (CV. Rayyan Dwi Bharata, 2026)
Education is a fundamental human right guaranteed by the constitution and international instruments, serving as the foundation for building an advanced nation. However, equitable fulfillment of the right to education remains a significant challenge in Indonesia, particularly in Indragiri Hilir Regency. This region faces various obstacles such as difficult geographical conditions, damaged school infrastructure, limited road access, and suboptimal teacher welfare. This study employs a literature review method with a qualitative approach to examine the condition of equitable access to education and strategies for implementing inclusive education in Indragiri Hilir. The findings indicate a high disparity in access and quality of education between urban and rural areas, exacerbated by inadequate facilities and resources. Inclusive education is viewed as a strategic solution to ensure equal access to education, emphasizing the principles of non-discrimination, acceptance of diversity, and fairness. Recommended strategies include improving educational infrastructure, enhancing road and transportation access, and increasing teacher welfare and protection. Collaboration among government, society, and the private sector is essential to ensure every child in Indragiri Hilir can access quality education without barriers, thus achieving the fulfillment of the right to education in a fair and sustainable manne.